1997
DOI: 10.1002/(sici)1097-0215(19970717)72:2<236::aid-ijc6>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Human tenascin-C: Identification of a novel type III repeat in oral cancer and of novel splice variants in normal, malignant and reactive oral mucosae

Abstract: Tenascin-C is a mosaic, linear glycoprotein that is upregulated during many normal and pathological processes involving either cell migration or tissue morphogenesis, such as invasion of malignant cells and wound healing. Human tenascin-C contains 8 consecutive type III fibronectin (TNCfn) domains that are involved in alternative splicing and potentially generate a large number of isoforms that code for tenascin-C proteins with subtly different functions. Human tenascin-C splice variants were investigated by R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…However, 2 further alternatively spliced FNIII domains (additional domains 1 and 2: FNIII AD1 27 and AD2 28 (accession numbers U88892.1 and EU295718.1 respectively) were later discovered. FNIII AD1 was identified within human U251 glioma cDNA clones as a single exon between FNIII repeats B and C. This study also showed that while AD1 was present in human glioblastoma, neuroblastoma and osteosarcoma tumor cells, it was absent in healthy human lung fibroblasts and umbilical vein endothelial cells (HUVECs) providing the first indication that tenascin-C splicing may play a role in tumorigenesis.…”
Section: Tenascin-c Exon Structurementioning
confidence: 99%
See 2 more Smart Citations
“…However, 2 further alternatively spliced FNIII domains (additional domains 1 and 2: FNIII AD1 27 and AD2 28 (accession numbers U88892.1 and EU295718.1 respectively) were later discovered. FNIII AD1 was identified within human U251 glioma cDNA clones as a single exon between FNIII repeats B and C. This study also showed that while AD1 was present in human glioblastoma, neuroblastoma and osteosarcoma tumor cells, it was absent in healthy human lung fibroblasts and umbilical vein endothelial cells (HUVECs) providing the first indication that tenascin-C splicing may play a role in tumorigenesis.…”
Section: Tenascin-c Exon Structurementioning
confidence: 99%
“…27 Human FNIII AD2 was discovered between FNIII B and AD1 in oral mucosa carcinoma samples and was named so on account of being in the same respective location as the avian FNIII AD2; situated between FNII B and AD1, in addition to it sharing 70% amino acid and 55% nucleotide sequence homology with the avian FNIII AD2. 28,29 Thus human TNC contains 30 exons (Fig. 1).…”
Section: Tenascin-c Exon Structurementioning
confidence: 99%
See 1 more Smart Citation
“…30 Transcripts for splice variants including the AD2 repeat are found in oral cancer tissues, but not in normal and pre-malignant tissues. 31 Immunohistochemistry using a recombinant antibody to the spliced repeat C has shown that the repeat is not detectable in normal adult tissues, not or barely detectable in malignant epithelial tumors, but abundant in glioblastomas. 32 From quantitative analysis using antibodies against alternative spliced domains, an increased fraction of Tn-C containing A1-A4 appears related to the tumor stage of colorectal cancer, while domain D is down-regulated in metastasizing cancers.…”
mentioning
confidence: 99%
“…Reverse transcription was performed at 37˚C for 60 min in a 20-ml reaction containing 2 mg RNA, 500 ng oligo(dT) primers, 4 ml 53 RT buffer (250 mM Tris-HCl [pH 8.3], 375 mM KCl, 15 mM MgCl 2 , and 50 mM DTT), 0.5 ml of 40 mM 29-deoxynucleoside 59-triphosphate, 0.5 ml of 200 U/ml RNase inhibitor (Promega, Madison, WI), 3.5 ml diethyl pyrocarbonate-treated water, and 1 ml of 200 U/ml M-MLV reverse transcriptase (Promega, Madison, WI). The oligonucleotide primers used are listed in Table I ( [23][24][25][26]. PCR cycles were carried out on a DNA thermal cycler (Hybaid Omnigene, Middlesex, U.K.).…”
Section: Rt-pcrmentioning
confidence: 99%